2022
DOI: 10.1016/j.jtocrr.2021.100260
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Myositis in a Patient With EGFR-Mutated NSCLC on Osimertinib: Case Report

Abstract: Osimertinib is the standard of care for the first-line treatment of EGFR -mutated NSCLC. We report a case of a 52-year-old woman who developed life-threatening myopathy because of treatment with osimertinib. Limited instances of myositis have been previously reported in the literature; however, none have resulted in life-threatening oropharyngeal and respiratory muscle weakness as seen in this case. Care should be taken in administering osimertinib concurrently with other medications met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Atorvastatin is weak inhibitor of CYP3A4, 17) therefore gefitinib metabolism may have been delayed, resulting in the symptom development of symptoms. A similar process was confirmed in previous reports regarding osimertinib-induced symptoms, [5][6][7] suggesting that elevated CK may be a predictor of myositis. Shusei et al reported a case of CK elevation without any symptoms 10 d after osimertinib initiation, with stabilization at approximately 600 U/L.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Atorvastatin is weak inhibitor of CYP3A4, 17) therefore gefitinib metabolism may have been delayed, resulting in the symptom development of symptoms. A similar process was confirmed in previous reports regarding osimertinib-induced symptoms, [5][6][7] suggesting that elevated CK may be a predictor of myositis. Shusei et al reported a case of CK elevation without any symptoms 10 d after osimertinib initiation, with stabilization at approximately 600 U/L.…”
Section: Discussionsupporting
confidence: 89%
“…12) Although EGFR-TKI-induced myositis is uncommon, it has recently been reported with osimertinib. [5][6][7] We speculate that EGFR-TKI-induced myositis The patient had taken 10 mg of atorvastatin before gefitinib initiation. CK elevated on day 47.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations